2022
DOI: 10.1002/esp.5383
|View full text |Cite
|
Sign up to set email alerts
|

Topographic controls on ice flow and recession for Juneau Icefield (Alaska/British Columbia)

Abstract: Globally, mountain glaciers and ice caps are losing dramatic volumes of ice. The resultant sea‐level rise is dominated by contributions from Alaska. Plateau icefields may be especially sensitive to climate change due to the non‐linear controls their topography imparts on their response to climate change. However, Alaskan plateau icefields have been subject to little structural glaciological or regional geomorphological assessment, which makes the controls on their present and former mass balance difficult to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 113 publications
0
34
0
1
Order By: Relevance
“…As well as triggering the ice-elevation and the ice-albedo feedbacks, the rise in temperatures also causes the ELA to rise above the elevation of many major icefalls. Davies et al (2022), identified 13 major outlet glaciers at risk of disconnection due to ice thinning intersecting their icefalls. By 2040, our model projects that all the major icefalls mapped by Davies et al (2022) around the peripheries of the plateau will have a negative annual mass balance.…”
Section: The Potential Response Of Glaciers Across the Juneau Icefieldmentioning
confidence: 99%
See 4 more Smart Citations
“…As well as triggering the ice-elevation and the ice-albedo feedbacks, the rise in temperatures also causes the ELA to rise above the elevation of many major icefalls. Davies et al (2022), identified 13 major outlet glaciers at risk of disconnection due to ice thinning intersecting their icefalls. By 2040, our model projects that all the major icefalls mapped by Davies et al (2022) around the peripheries of the plateau will have a negative annual mass balance.…”
Section: The Potential Response Of Glaciers Across the Juneau Icefieldmentioning
confidence: 99%
“…Davies et al (2022), identified 13 major outlet glaciers at risk of disconnection due to ice thinning intersecting their icefalls. By 2040, our model projects that all the major icefalls mapped by Davies et al (2022) around the peripheries of the plateau will have a negative annual mass balance. Across the 2031-2060 time period, the multi-model mean of our future projections indicates a range of negative SMB at icefall locations, between -0.5 m w.e.…”
Section: The Potential Response Of Glaciers Across the Juneau Icefieldmentioning
confidence: 99%
See 3 more Smart Citations